Profil Kepribadian Gamers Esports DotA 2 di Kota Bandung - Aryo Triutama; Milda Yanuvianti (Jurnal Riset Psikologi, 2021)
Abstract. Currently online games have become one of the branches of sports known as Esports. In the competition of Esports, DotA 2 became game the most profitablein terms of prizes. 2018 became the best year in DotA 2 Esports Indonesia, but the development of Esports Dota 2 in Indonesia has decreased in 2019. Despite having problems, the DotA 2 game is still popular in several internet cafes in the city of Bandung. According to Collins, Freeman, & Chamarro-Premuzic (2012) personality traits related to the behavior of playing online games. As the development of knowledge, personality traits can be measured through the concept of Big Five Personality Traits, according to Strus, Cieciuch, & Rowiński (2014) In big five personality traits there are 5 dimensions, namely Emotional Stability vs. Neurotism, Extraversion, Agreeableness, Conscientiousness, and Openness / Intellect. In this study, the method used is descriptive with a purposive sampling technique of 34 Esports gamers in the city of Bandung. The purpose of this study was to determine the personality profile of Esports gamers in the city of Bandng. Researchers used the IPIP BFM-25 standard measuring instrument made by Akhtar & Azwar, (2018). The results of this study show the dimensions of Conscientiousness (82.4%), Agreeableness (88.2%), and Intellect (91.2%) became dominant in the score with a high category, and Emotional Stability (64.7%) become the dominant dimension in the low score category. Abstrak. Saat ini game online sudah menjadi salah satu cabang olahraga yang dikenal dengan Esports. Dalam kompetisi Esports, DotA 2 menjadi game yang paling profit dari segi hadiah. Tahun 2018 menjadi tahun terbaik di Esports DotA 2 Indonesia, namun perkembagan Esports Dota 2 di Indonesia mengalami penurunan pada tahun 2019. Meskipun memiliki permasalahan namun game DotA 2 masih menjadi populer di beberapa warnet di kota Bandung. Menurut Collins, Freeman, & Chamarro-Premuzic (2012) personality traits terkait dengan perilaku bermain game online. Seiring perkembangan ilmunya, personality traits dapat diukur melalui konsep Big Five Personality Traits, menurut Strus, Cieciuch, & Rowiński (2014) Dalam big five personality traits terdapat 5 dimensi, yaitu Emotional Stability vs Neurotism, Extraversion, Agreeableness, Conscientiousness, dan openness / Intellect. Dalam penelitian ini, metode yang dipakai adalah deskriptif dengan teknik sampling purposive terhadap 34 gamers Esports di kota Bandung. Tujuan dari penelitian ini untuk mengetahui profil kepribadian gamers Esports di kota Bandng. Peneliti menggunakan alat ukur baku IPIP BFM-25 yang dibuat oleh Akhtar & Azwar, (2018). Hasil dari penelitian ini menunjukan dimensi Conscientiousness (82,4%), Agreeableness (88,2%), dan Intellect (91,2%) menjadi dominan pada skor dengan kategori tinggi, dan Emotional Stability (64,7%) menjadi dimensi yang dominan pada kategori skor rendah.